Costs of colorectal cancer screening with colonoscopy, including post-endoscopy events, among adults with Medicaid insurance. (4th May 2022) - Fisher, Deborah A.; Princic, Nicole; Miller-Wilson, Lesley-Ann; Wilson, Kathleen; Limburg, Paul
Abstract: Objective: To examine the healthcare utilization and costs associated with colorectal cancer (CRC) screening by colonoscopy, including costs associated with post-endoscopy events, among average-risk adults covered by Medicaid insurance. Methods: This cohort study evaluated a population of adults (ages 50–75 years) with CRC screening between 1/1/2014 and 12/31/2018 (index = earliest test) from the IBM MarketScan Multi-State Medicaid database. Individuals at above-average risk for CRC or with prior CRC screening were excluded. CRC screening was reported by screening type: colonoscopy, fecal immunochemical test [FIT], fecal occult blood test [FOBT], multi-target stool DNA [mt-sDNA]. Frequency and costs of events potentially related to colonoscopy (defined as occurring within 30 days post-endoscopy) were reported overall, by event type, and by individual event. Results: We identified a total of 13, 134 average-risk adults covered by Medicaid insurance who received screening by colonoscopy; 63.6% (8350) had Medicare dual-eligibility while 36.4% (4785) did not have Medicare dual-eligibility. The mean (SD) cost of a colonoscopy procedure was $684 ($907) and mean (SD) out-of-pocket costs were $6 ($132). Serious gastrointestinal (GI) events (perforation and bleeding) were observed in 4.6% of individuals with colonoscopy, 4.3% had other GI events, and 3.0% had an incident cardiovascular/cerebrovascular event. Mean (SD) event-related costs were $1233 ($5784) among individuals with a serious GI event, $747 ($1961) among individuals with other GI events, and $4398 ($19, 369) among individuals with a cardiovascular/cerebrovascular event. Conclusions: This large, claims-based cohort study reports average (SD) out-of-pocket costs for Medicaid beneficiaries at $6 ($132), which could be one factor contributing to the accessibility of CRC screening by colonoscopy. The incidence of events potentially associated with colonoscopy (i.e. within 30 days after the screening) was 3–4%, and the event-related costs were considerable.